ENPP: Extended Non-preemptive PP-aware Scheduling for Real-time Cloud Services - Fereshteh Hoseini; Mostafa Ghobaei Arani; Alireza Taghizadeh (Institute of Advanced Engineering and Science, 2016)
By increasing the use of cloud services and the number of requests to processing tasks with minimum time and costs, the resource allocation and scheduling, especially in real-time applications become more challenging. The problem of resource scheduling, is one of the most important scheduling problems in the area of NP-hard problems. In this paper, we propose an efficient algorithm is proposed to schedule real-time cloud services by considering the resource constraints. The simulation results show that the proposed algorithm shorten the processing time of tasks and decrease the number of canceled tasks.